Modelo computacional de otimização para dimensionamento de redes de distribuição de água abastecidas por múltiplos bombeamentos. - Gouveia, Roberta Macêdo Marques (2012)
The high costs involved in water distribution systems, particularly with regard to the design and operation thereof, reflect the importance of studying ways to minimize the loss of water and electricity, in order to increase the efficiency of these systems. In an attempt to minimize and avoid such loss, This study commit to investigate and propose a model optimized sizing of networks, with emphasis on hydraulic efficiency, energy and economic. The main objective is to minimize system costs, understood by the network pipe costs, the energy of pumping main (main system of impulsion) and the energy of pumping secondary, represented by boosters. The proposed methodology for the sizing considers the energy costs of multiple pumping, plus the cost of implantation of the pipes. Using this methodology it is possible to achieve a design with lower pressures and longer appropriate, with consequent reduction in energy and water losses throughout the system. To achieve the proposed objectives, the methodology used in this study comprehend an iterative algorithm and dynamic of optimization. The said algorithm originated the program Toolkit of Sizing Optimized (TDO), that have been implemented using the EPANET Programmer's Toolkit. To validate the theory, case studies were conducted with three water distribution networks: network Grande Setor Expanded , network R9 Adapted and network Hanoi The results obtained, using the TDO, demonstrate that the sizing most suitable for operation of the networks studied were obtained using sectorization, through the inclusion of secondary pumping.